IS INTELLECTUAL CAPITAL ENHANCING THE FINANCIAL PERFORMANCE OF BUM DESA? CASE STUDY IN TAMBANG SUB-DISTRICT, KAMPAR DISTRICT, RIAU PROVINCE - Ayub Rasidy (Jurnal Agribisnis, 2020)
Intellectual capital is an intangible asset that consist of knowledge and networks that can improving the economic value of business. BUM Desa is a village owned enterprise was hopefully to become a pillar of village economic development in Indonesia after issued UU No. 6/2014. This study aims to identified and measure the intellectual capital and analyze the relationship of intellectual capital on financial performance of BUM Desa. Research was done by case study in Tambang Sub-district, Riau Province. Intellectual capital was measured by the Likert and financial performance of BUM Desa was measured in profitability and cost reduction. Descriptive analysis was used to determine the relationship between intellectual capital and financial performance. The results showed that the intellectual capital of BUM Desa was forming by the structural capital, the relationship capital and the human capital respectively. BUM Desa has the ability to generate profits from assets better than the equity and BUM Desa has the ability to minimized costs to generate profits. BUM Desa that have higher intellectual capital have better finances. In the future, empowering of BUM Desa needs to be considered the capital intellectual development.